Nurses’ Perceptions of Customized Nursing Care in Acute Medical and Perioperative Environments - Nourah Reja A Al-Mutairi, Eman Hamdan Hamoud Almutairi, ‏Norah Awad Alanazi, ‏Reham Abdallah Alsadi; Maha Suhail Al-Mutairi, ‏Nawal Awad Alanazi, ‏Aliaa Awad Alanazi, ‏Bashayr Mohammed Alanazi (Journal of International Crisis and Risk Communication Research, 2024)
Background/Objectives: Individualized nursing care is essential as it allows for systematic assessment and intervention, considering a patient's preferences, values, and context, which can contribute to a positive care trajectory. However, its operationalization has proven challenging. This research aimed to evaluate nurses' perceptions of individualized care and analyze their relationship with sociodemographic variables. Methods: This was a cross-sectional study conducted with 122 eligible and registered nurses at a hospital, including various clinical units such as ophthalmology, cardiology, internal medicine, and the medical emergency unit. The nursing version of the Individualized Care Scale (ICS-Nurse), which includes three sub-dimensions (clinical situation, personal life situation, and decisional control), was used for the assessment. Cronbach's alpha and principal component analysis were used for data analysis, and the STROBE checklist was used to report the study. Results: No statistically significant differences were found based on the nurses' age, gender, level of education, or years of professional experience within the sub-dimensions of individualization. The nurses overall had a good perception of the importance of individualized care, but faced difficulties in its implementation during their last shift. The items considered most important were related to the physical and emotional needs arising from illness and assistance in decision-making through educational instructions. Aspects related to the personal lives of patients, such as family inclusion, everyday habits, and previous hospitalization experiences, received the lowest scores. Conclusions: Recognizing priority areas for improvement in the individualization of nursing care can contribute to developing training programs and policies that promote a more holistic approach. Future studies should consider patient outcomes related to their needs for individualization.